Tri-axial accelerometry as an injury predictor tool in elite soccer - Brown, W.; Greig, M. (International Journal of Athletic Therapy & Training, 2017)
The epidemiology and etiology of ankle sprain injuries in soccer have been well described. Retrospective analysis of epidemiological data identified an English Premier League player sustaining a high lateral ankle sprain. GPS data collated during the training session in which the injury was sustained, and subsequent rehabilitation sessions, were analyzed to quantify uniaxial PlayerLoad metrics. The injured player revealed a 3:1 asymmetrical loading pattern in the mediolateral plane and multiaxial high loading events which might present the inciting event to injury. The high magnitude, asymmetrical and multiplanar loading is consistent with lateral ankle sprain etiology.